Engineering students' attitudes toward e-learning in a polytechnic - Ong, Bernard Ah Chwee. (2008)
The goal of this study is to identify the attitudes and preferences of final year engineering students toward their e-learning. E-learning is practiced and recommended for teachers’ theory, as well as policy and implementation of e-learning at the polytechnic.